Pengaruh Liberalisasi Arus Modal terhadap Pertumbuhan Ekonomi ASEAN-5 - Devilia Sitorus; Crisanty Sutristyaningtyas Titik (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
This study aims to examine the relationship between capital flow liberalization and economic growth in ASEAN-5. This research is a quantitative study that uses data: GDP, Gross Capital Formation, financial disclosure seen from the Chinn-Ito index for the period 2000-2017 in 5 ASEAN countries namely Indonesia, Malaysia, the Philippines, Singapore, and Thailand. Data were processed using panel data regression analysis and specifically for Indonesia, Partial Adjustment Model (PAM) regression was performed. The results of this study indicate that financial openness seen from the Chinn-Ito index has a negative and significant influence on the economic growth of ASEAN-5 countries. Capital flows have a positive and significant impact on the economic growth of ASEAN-5 countries. Meanwhile, the PAM (Partial Adjustment Model) regression model shows that capital flows have a positive and significant influence on Indonesia's economic growth both in the short and long term, while financial openness has a negative and significant impact on Indonesia's economic growth both in the short and long term.